Online Thrift Shop Phenomenon as a Business Opportunity for Young Entrepreneurs in Manado City: A Multicultural Perspective - Niu, Fitria Ayu Lestari; Jan, Radlyah Hasan; Tabe, Ridwan; Songkaton, Yulia (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2023)
The thrift shop phenomenon is on the rise in Indonesia, especially among young entrepreneurs who utilize the ease of online marketing. This research aims to examine online thrift shops as a business opportunity for young entrepreneurs in Manado City through a multiculturalism approach. Qualitative method with in-depth interviews with 8 main informants from Manado, Minahasa, and Gorontalo ethnicities. Results show that cultural background influences entrepreneurial orientation. Ethnic Minahasa tends to sell casual fashion, in contrast to ethnic Gorontalo who prioritizes Muslim clothing. The migrants' marketing strategy utilizes more social commerce, while the ethnic Manado still relies on community-based marketing. Young entrepreneurs are also encouraged by the flexibility and profit potential of thrift shops, although the risk of product damage and network constraints are challenges. Thus, this study found that cultural background and local values shape thrift shop business orientation and entrepreneurial behavior. Understanding this multicultural perspective can encourage the development of a thrift shop ecosystem that is more inclusive and responsive to the cultural diversity of the people of Manado City.